2000
DOI: 10.1210/jcem.85.11.6969
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Na+/ISymporter and Pendred Syndrome Genes in Trophoblast Cells1

Abstract: Placental iodide transport is critical for the fetal thyroid function, but the molecular mechanisms of this transport are not understood. The expression of two recently identified iodide transporters, namely the sodium/iodide symporter (NIS) and pendrin, the product of the gene responsible for the Pendred syndrome (PDS), was studied using real-time kinetic quantitative PCR and immunohistochemistry 1) in placental tissues collected at different gestational ages and 2) in primary cultures of villous cytotrophobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The 5 kb SLC26A4 transcript encodes a 780 amino acid protein, designated pendrin, which is predicted to contain 11 putative TMD [54]. Pendrin is expressed primarily in the thyroid gland and inner ear, with weaker signals in the kidney, brain, mammary gland, endometrium and placenta [54][55][56], and it shares significant amino acid identities with sulfate transporters, including SLC26A1 (SAT-1) (30%), SLC26A2 (DTDST) (30%) and SLC26A3 (DRA) (44%) [54]. However, despite these amino acid similarities, pendrin was unable to induce any sulfate transport in Xenopus oocytes or Sf9 insect cells [57,58].…”
Section: Slc26a4 Mutations In Pendred Syndromementioning
confidence: 99%
“…The 5 kb SLC26A4 transcript encodes a 780 amino acid protein, designated pendrin, which is predicted to contain 11 putative TMD [54]. Pendrin is expressed primarily in the thyroid gland and inner ear, with weaker signals in the kidney, brain, mammary gland, endometrium and placenta [54][55][56], and it shares significant amino acid identities with sulfate transporters, including SLC26A1 (SAT-1) (30%), SLC26A2 (DTDST) (30%) and SLC26A3 (DRA) (44%) [54]. However, despite these amino acid similarities, pendrin was unable to induce any sulfate transport in Xenopus oocytes or Sf9 insect cells [57,58].…”
Section: Slc26a4 Mutations In Pendred Syndromementioning
confidence: 99%
“…The experiments described above clearly demonstrated that PAX8 is expressed in JAR cells and that this expression is regulated by hCG. To identify the effects of this expression, we overexpressed PAX8 in JAR cells by means of transfection and performed quantitative RT-PCR to measure the levels of mRNA for the two PAX8-target genes, WT1 (25, 26) and NIS (10), both of which are known to be expressed in human placenta (4,17,27). As shown in Fig.…”
Section: Transcriptional Effects Of Pax8 In Jar Cellsmentioning
confidence: 99%
“…Recent reports suggest that PAX8 is also involved in modulating the expression of D2 deiodinase (15,16), one of the enzymes responsible for the deiodination of iodothyronines. More recent evidence indicates that the NIS (17) and the iodothyronine deiodinases, D2 and D3, which were originally considered to be thyroid specific, are also expressed by placental trophoblasts (18,19), in which their presence is essential for ensuring adequate supplies of iodide for the synthesis of fetal thyroid hormones. These discoveries suggested that placental expression levels of these genes might be modulated by PAX8, as they are in the thyroid.…”
mentioning
confidence: 99%
“…In these tissues, it is involved in iodide flux into the thyrocyte follicular lumen, maintenance of the pH, ion composition and volume of the endolymph, and moreover body acid-base equilibrium, fluid homeostasis and blood pressure regulation. Pendrin is also expressed, although at a minor level relative to the aforementioned tissues, in the placenta [9], lactating mammalian glands [10], testis [11], prostate [11], endometrium [12], platelets [13], and lung [14]. …”
Section: Introductionmentioning
confidence: 99%